The Legal Certainty of Execution of the Death Penalty in Indonesian Criminal Justice System - Willy Tanjaya; Teguh Prasetyo; Muhadar Muhadar; Lilik Mulyadi (Postgraduate of Jayabaya University, 2015)
This study aims to answer three main problems, namely: (1) How the provisions of the deadline for execution on the death row prisoners in the Indonesian justice system?; (2) What method of execution on death row prisoners in the Indonesian justice system?; and (3) How is the policy of capital punishment in Indonesia in the future?. This research uses the primary, secondary and tertiary legal materials. The research methods being used in this research is normative method with the application of the statute approach, the case approach and the comparative approach. The results of this study shows the following conclusions: (1) the criminal law system in Indonesia is not set the deadline for execution on death row prisoner who had obtained a court decision that is legally binding and or the clemency petition has been rejected signal by the president; (2) The method of execution that has been implemented in Indonesia is a method of firing squad the u.s. stipulated in Law No. 2/Pnps/1964; (3) The policy the SE for the death penalty law in Indonesia in the future will not be shifted away from the current state.